Electron-percolation-driven electric-field harmonization reprograms Zn nucleation for ultrastable Zn metal anodes - Jia-Sheng Lin; Daniel Chang; Che-Ning Yeh; Yi-Chun Yang; Hsing-Yu Tuan (Chemical Engineering Journal, 2026)

Air movement and temperature regime in large stacked apple bins during the initial phases of cold storage - Tuany Gabriela Hoffmann; Poonam Bidgar; Jincheng Yu; Daniel Alexandre Neuwald; Reiner Jedermann; Manfred Linke; Pramod Mahajan (Biosystems Engineering, 2026)

Exploiting highly humidity-resistant flexible NH3 gas sensors based on hot-stirred PEDOT: PSS coupled with dual-phase VOx nanofibers - Fang-Yu Chiang; Sanjaya Brahma; Kun-You Chen; Yi-Ting Li; Vrnata Martin; Matej Daniel; Wei-Jung Chen; Le Vo Phuong Thuan; Chia-Yun Chen (Chemical Engineering Journal, 2026)

Defect engineering oxygen vacancies via synergistic tungsten substitution and water quenching in V2O5 cathodes for high-performance zinc-ion batteries - Jianwei Wang; Lin Xu; Yating Yu; Jianzhao Liu; Qianhui Zhang; Wenlin Zhang; Xinyue Wang; Jihong Bian; Yanzhong Zhen; Daniel Q. Tan (Chemical Engineering Journal, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

The spatiotemporal distributions of global paleo-Köppen climate zones during the Mesozoic-Cenozoic - Chenmin Yu; Daniel J. Lunt; Laiming Zhang; Linshu Hu; Chengshan Wang (Earth-Science Reviews, 2026)

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Vacancy assisted spin-state modulation strategy for efficient nitrate electrosynthesis - Yaoyang Yu; Yifan Xu; Yingguang Zhang; Daniel H.C. Wan; Xin Li; Michael K.H. Leung (Chemical Engineering Journal, 2026)

Integrating systemic toxicity and toxicokinetic data to inform the need for subchronic dog studies in human health safety assessments of agrochemicals - Lynea Murphy; Robert Mingoia; Enrica Bianchi; Viera Lukacova; Jeanne Domoradzki; Claire Terry; Sean Gehen; Rachel Brunner; Angela Myer; Brandall L. Ingle; Daniel Hoer; Yu-Mei Tan (Regulatory Toxicology and Pharmacology, 2026)

Aviation-fuel-grade aromatic–cycloalkane blends via isoeugenol hydrodeoxygenation using nickel aluminate spinel catalyst - Jose Luis Ayastuy; Dmitry Yu. Murzin; Daniel Gallego-García; Mark E. Martínez-Klimov; Päivi Mäki-Arvela; Johan Wärnå; Unai Iriarte-Velasco; Miguel Angel Gutiérrez-Ortiz (Environmental Chemistry Letters, 2026)
Aviation is a major contributor to greenhouse gas emissions, and thus developing renewable alternatives such as lignin-derived biofuels is critical. Current catalytic routes for hydrodeoxygenation of bio-oil model compounds, such as isoeugenol, fail to produce the desired aromatics to cycloalkane ratios required for aviation fuels. We hypothesized that tailoring metal-support interactions in a nickel aluminate spinel catalyst can enable selective formation of hydrocarbon blends meeting fuel specifications. Hydrodeoxygenation of isoeugenol was conducted in a batch reactor using a nickel aluminate spinel catalyst synthesized via a one-pot sol-gel method. Reactions were conducted at 250–300 °C and 20–40 bar hydrogen pressure, and products were analyzed by gas chromatography-mass spectrometry to determine yields of aromatics, cycloalkanes, and intermediates. Catalyst structure and surface properties were characterized using X-ray diffraction, X-ray photoelectron spectroscopy, X-ray absorption spectroscopy, and electron microscopy to establish structure–performance relationships. Under optimized conditions of 275 °C at 20 bar H 2 , aromatic and cycloalkane yields reached 16 wt% and 30 wt%, respectively. Reaction trends showed that elevated temperatures favor cycloalkane formation while hydrogen pressure controls intermediate conversion. The moderate Lewis acidity combined with medium-sized Ni 0 crystallites promote selective hydrogenation and deoxygenation while minimizing over-hydrogenation. This catalytic system produces fuel-grade hydrocarbon mixtures in a single step, exceeding previously reported performance. These findings provide a practical route for lignin valorization and the production of renewable aviation fuels with reduced greenhouse gas emissions.

MFC 5.0: An exascale many-physics flow solver - Benjamin Wilfong; Henry A. Le Berre; Anand Radhakrishnan; Ansh Gupta; Daniel J. Vickers; Diego Vaca-Revelo; Dimitrios Adam; Haocheng Yu; Hyeoksu Lee; Jose Rodolfo Chreim; Mirelys Carcana Barbosa; Yanjun Zhang; et al. (Computer Physics Communications, 2026)

Identifying potential invasion hotspots for non-native fluvial fishes throughout the conterminous United States - Hao Yu; Arthur R. Cooper; Jared A. Ross; Wesley M. Daniel; Jack E. Taylor; Alina Sargsyan; Dana M. Infante (Biological Invasions, 2026)
Identifying habitats that non-native fluvial fishes are likely to invade provides information for proactive management, conservation planning, and understanding the ecology of biological invasions. We identified streams in the conterminous United States with high invasion risk from 20 non-native fluvial fish species. Specifically, we (1) developed habitat suitability models for each species using nine natural and six anthropogenic predictors within nine large ecoregions, identifying the potential invasion hotspots; (2) evaluated the relative importance of natural and anthropogenic predictors for each species; and (3) assessed potential invasion risk to protected stream habitats. Predicted invasion hotspots included much of Florida, coastal regions of Texas and Louisiana, and areas surrounding major metropolitan centers such as Chicago, New York, and Phoenix. Model predictions indicate that goldfish ( Carassius auratus ), pirapitinga ( Piaractus brachypomus ), and pond loach ( Misgurnus anguillicaudatus ) could occupy extensive suitable habitats across the conterminous United States. The most influential natural predictor across species was network catchment area (a surrogate for stream size), while the most influential anthropogenic predictor was human population density. Goldfish were predicted to be present in protected areas across all nine ecoregions, highlighting their high invasion potential. Collectively, our results provide critical information on regions vulnerable to invasion and the species most likely to become established and identify areas at risk of invasion within protected landscapes.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Extreme weather events accelerate biological invasions: Mechanisms and conservation implications - Yu Liu; Daniel A. Cossey; Haiyue Jing; Shiguo Li; Jing Hou (Biological Conservation, 2026)

Soil pH Modulates the Global Stabilized Soil Organic Carbon - Cuijuan Liao; Mengxiao Yu; Ying‐Ping Wang; Philippe Ciais; Rose Z. Abramoff; Wenting Feng; Daniel S. Goll; Yuxin Zhang; Manseng Chio; Fayong Liu; Xuli Tang; Zilong Zhang; et al. (Global Change Biology, 2026)
Soil mineral‐associated organic carbon (MAOC) constitutes over 50% of total soil organic carbon (SOC) and serves as a key determinant of its long‐term stabilization. Although soil pH is recognized as a “master variable” in biogeochemical cycles, it remains unclear how soil pH influences MAOC and SOC at large spatial scales. To address this knowledge gap, we conducted a continental‐scale survey in China and synthesized global observations from literature, totaling 1300 independent observations. We analyzed the relationships between SOC and MAOC across pH gradients and assessed the contributions of other environmental factors to MAOC variability. Our results showed that higher SOC content is generally positively correlated with higher MAOC. However, this relationship is strongly influenced by soil mineralogy, texture, and climatic conditions. We identified distinct pH‐dependent pathways controlling MAOC formation. In acidic soils (pH ≤ 5.5), Fe/Al (hydr)oxides explain most of the variation in MAOC content and in MAOC fraction (the ratio of MAOC to SOC). In neutral‐to‐alkaline soils (pH > 6.5), however, clay content and mean annual temperature emerge as the primary regulators. Net primary productivity (NPP) augments the particulate organic carbon (POC) pool, thereby diluting the MAOC fraction. This divergence challenges the universal applicability of clay‐centric SOC models in acidic soils. Our findings provide a conceptual framework for biogeochemical models, urging the integration of pH‐dependent metal oxide dynamics to improve predictions of SOC persistence under diverse future scenarios.

Micro-CT cranial anatomy and phylogenetic context of palatal characters in arvicoline rodents (Cricetidae) - Leonid L. Voyta; Daniel A. Melnikov; Lyudmila Yu. Kryuchkova (Zoologischer Anzeiger, 2026)

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Impacts of atmospheric CO2 enrichment on nitrous oxide emissions in wheat and rice cropping systems at global and local scales - Shengji Yan; Guiyao Zhou; Daniel Revillini; Yunlong Liu; Haoyu Qian; Aixing Deng; Yanfeng Ding; Yu Jiang; Manuel Delgado-Baquerizo; Xin Zhang; Weijian Zhang (European Journal of Agronomy, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

In Response to “Toward Balanced Curricula: Advancing Nondiet and Weight-Neutral Education in Dietetics” - Nicholas Slagel; Daniel Hall; Yu Wang; Zoe Duran; Katelyn Crawley; Dawn Clifford; Cristen Harris; Jeffrey Hunger; Emma Laing (Journal of Nutrition Education and Behavior, 2026)

Architects of plant immunity: Structure-informed strategies for engineering plant nucleotide-binding leucine-rich repeat receptors - Daniel S. Yu; Mark J. Banfield (Current Opinion in Plant Biology, 2026)

Tuning the morphology of aerosolised cellulose nanocrystal particulates via controlled aggregation - Daniel Warnes; Wenyang Xu; Jia Hui Lim; Richard M. Parker; Bruno Frka-Petesic; Ray Freshwater; Camila Honorato-Rios; Yu Ogawa; Chiara Giorio; Silvia Vignolini (Carbohydrate Polymers, 2026)

Phyllosphere to soil: How long-term fencing reshapes grassland microbial community construction and the functional genes - Jian Li; Yu Zhu; Daniel F. Petticord; David W. Frey; Lijie Huang; Ming-Kang Jin; Michiel Op de Beeck; Quan-Hui Ma; Shu-Huan Jin; Hong Ying; Xi-Mei Xue; Ling Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

First detailed description of male-male combat in the genus Dopasia Gray, 1875 (Reptilia: Anguidae) - Martina Lawson; Yu-Hsiang Su; Si-Min Lin; Daniel Jablonski (acta ethologica, 2026)

Phosphorus dynamics in the drilosphere: Unraveling earthworm-mediated soil biogeochemistry - Zhen-Yu Qiang; Gang Li; Daniel Menezes-Blackburn; Zhao-Feng Yuan; Tida Ge; Yvan Capowiez; Dong-Xing Guan (Critical Reviews in Environmental Science and Technology, 2026)

Asymmetrical contamination of anionic PFAS across global freshwater reservoirs - Zhao-Feng Guo; Mohamed Ateia; Edoardo Borgomeo; Wiebke J. Boeing; Daniel Malnes; Yu-Qin He; Dong Liu; Yao-Yang Xu (Water Research, 2026)

Shear failure behavior and damage evolution mechanism of sandstone under pre-static loading and low-frequency dynamic disturbance - Jun Guo; Jiahao Zhang; Guorui Feng; Luyang Yu; Jinwen Bai; Daniel Dias; Xiaoze Wen; Jie Zhang; Liang Zhang (Soil Dynamics and Earthquake Engineering, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Comparative Population Genomics of Relictual Caribbean Island Gossypium hirsutum - Weixuan Ning; Guanjing Hu; Daojun Yuan; Mark A. Arick; Chuan‐Yu Hsu; Zenaida V. Magbanua; Olga Pechanova; Daniel G. Peterson; Yating Dong; Joshua A. Udall; Corrinne E. Grover; Jonathan F. Wendel (Molecular Ecology, 2026)
Gossypium hirsutum is the world's most important source of cotton fibre, yet the diversity and population structure of its wild forms remain largely unexplored. The complex domestication history of G. hirsutum combined with reciprocal introgression with a second domesticated species, G. barbadense , has generated a wealth of morphological forms and feral derivatives of both species and their interspecies recombinants, which collectively are scattered across a large geographic range in arid regions of the Caribbean basin. Here we assessed genetic diversity within and among populations from two Caribbean islands, Puerto Rico ( n = 43, five sites) and Guadeloupe ( n = 25, one site), which contain putative wild or introgressed forms. Using whole‐genome resequencing data and a phylogenomic framework derived from a broader genomic survey, we parsed individuals into feral derivatives and truly wild forms. Feral cottons display uneven levels of genetic and morphological resemblance to domesticated cottons, with diverse patterns of genetic variation and heterozygosity. These patterns are inferred to reflect a complex history of interspecific and intraspecific gene flow that is spatially highly variable in its effects. Wild cottons in both Caribbean islands appear to be relatively inbred, especially the Guadeloupe samples. Our results highlight the dynamics of population demographics in relictual wild cottons that experienced profound genetic bottlenecks associated with repeated habitat destruction superimposed on a natural ecogeographical distribution comprising widely scattered populations. These results have implications for conservation and utilisation of wild diversity in G. hirsutum .

Trait space and compactness: A new perspective on explaining variations in primary productivity - Jiahui Zhang; Kailiang Yu; Markus Reichstein; Li Xu; Ian J. Wright; Mirco Migliavacca; Ulisse Gomarasca; Daniel C. Laughlin; Xiaoyu Cen; Congcong Liu; Honglin He; Nianpeng He (Ecology, 2026)
A fundamental question in ecology is why plant communities have large trait space yet strong coordination among those traits across large scales, despite these patterns seeming contradictory. Answering this question requires quantitatively linking the geographic distribution of trait space and coordination with gross primary productivity (GPP). We leveraged an unprecedented large‐scale dataset of nine leaf traits for 5718 species‐site combinations with simultaneous field measurements of plant community composition in 64 naturally assembled communities to investigate trait spaces (hypervolume, quantity dimension) and trait compactness (coordination, efficiency dimension) and their influence on GPP. Trait space and compactness combined explained 72% of the variation of GPP. Interestingly, a larger trait space (more diverse trait combinations) drove higher GPP in resource‐poor communities, while higher trait compactness (greater coordination of traits) determined higher GPP in resource‐rich communities. Our findings provide a new perspective that natural plant communities increase both trait space and compactness to improve GPP, shedding light on the development of multidimensional functional ecology.

Methylsiloxanes in drinking water treatment plants: Occurrence, removal efficiencies and exposure risks across multiple stages of treatment process development - Yimeng Zhang; Zhenyang Yu; Jing Yang; Ge Yin; Yanbin Zhao; G․Daniel Sheng; Daqiang Yin (Water Research, 2025)

Evaluation of time from cancer diagnosis to referral at a rural Ugandan ambulatory surgical center - Abhishek R. Mogili; Allen T. Yu; Chelsia Melendez; Daniel Mukisa; Shafiga Babirye; Angellica Giibwa; Moses Binoga; Anna T. Kalumuna; Joseph O. Damoi; Nina Mirabadi; Kaothar Oladoja; Linda P. Zhang (Next Research, 2025)

Novel Hybrid Model to Predict Ribbon Solid Fractions in the Roller Compaction Process - Kiran Iyer; Senthil Kumarasamy; Pankaj Doshi; Allan Hutchins; Patrick Daugherity; Weili Yu; Ashwin Jain; Danielle Bubucis; Matthias Danner; Daniel Schwenk; Holger Schlack (AAPS PharmSciTech, 2025)

Associations of environmental toxicant exposure with adult sleep problems and the mediating roles of inflammation - Lu-Jia Li; Wen Zhang; Daniel Yee-Tak Fong; Ji-Bin Li; Yu-Hui Kou; Sha Li; Xiao-Yong Chen; Wei-Jie Gong (Environmental Pollution, 2025)

Ammonia emissions from an avian-rich island in the Great Barrier Reef: Environmental drivers and observational insights - Lili Wu; Eva Johanna Horchler; Zoran Ristovski; Junwen Liu; Fei Yu; Shijie Han; Wenhui Zhao; Lara Richards; Daniel Harrison; Junyu Zheng; Branka Miljevic (Atmospheric Environment, 2025)

Elevated alpha-1 antitrypsin and C-reactive protein: association on all-cause and cause-specific mortality in older adults - Cammie Tran; Hans G. Schneider; Que T. Lam; Johannes T. Neumann; Flavia Cicuttini; Chenglong Yu; Zhen Zhou; Mark R. Nelson; Andrew M. Tonkin; Daniel Clayton-Chubb; Sultana Monira Hussain; Peter D. Fransquet; et al. (GeroScience, 2025)

2D Numerical investigation of tsunami bore impact on an elastic emerged plate - Daniel Bara Padang Allo; Yu Hsiao; Shih-Chun Hsiao (Ocean Engineering, 2025)

Microstructure and CPO evolution of dynamically recrystallized olivine during complex deformation conditions: a full-field numerical modeling approach - Yuanchao Yu; Albert Griera; Enrique Gomez-Rivas; Paul D. Bons; Daniel Garcia-Castellanos; Baoqin Hao; Ricardo A. Lebensohn; Cassandra Seltzer; Maria-Gema Llorens (Journal of Structural Geology, 2025)

The metabolism and antioxidant properties of probiotics and prebiotics in fish: a review - Lishuko Ng’onga; Kwaku Amoah; Huapu Chen; Yu Huang; Bei Wang; Vicent Michael Shija; Alatwinusa Yohana Mpwaga; Muhammad Fachri; Jia Cai; Daniel Adjei-Boateng (Frontiers in Marine Science, 2025)
The issue of antimicrobial resistance in farm-raised fish presents a significant challenge for aquaculture operations. Long-term antibiotic treatment of fish for bacterial infections has led to bacteria thriving in the aquatic ecosystem and developing resistance to antibiotics. On the other hand, increasing research suggests that probiotics and prebiotics may be viable alternatives to antibiotics in regulating the immune system. Probiotics and prebiotics interact with fish metabolism in complex ways. These interactions offer promising alternatives to reduce antibiotic use in aquaculture. Introducing live microorganisms, known as probiotics, into an organism’s system can help improve overall health by altering the microflora and boosting immunity. Acting as immunostimulants, prebiotics directly impact the fish’s innate immune system. When used together, probiotics and prebiotics enhance immunomodulatory activity, providing numerous health benefits to aquatic animals. However, successfully replacing antibiotics with probiotics and prebiotics requires a deep understanding of metabolic pathways, optimization strategies, and innovative approaches. There has been a lack of extensive research on how probiotics and prebiotics impact lipid metabolism in various types of fish. This review aims to explore the intricate relationship between probiotics, prebiotics, and fish metabolism, with a specific focus on how these beneficial microorganisms and dietary fibers interact with fish antioxidant systems. We have also discussed the challenges faced by farmers when using probiotics and prebiotics. This review analyzes metabolic and antioxidant interactions mediated by probiotics and prebiotics in cultured fish species. It synthesizes findings on histological effects, enzymatic activity, and microbial interactions, with emphasis on lipid metabolism and immune modulation, and also discusses the practical implications for sustainable aquaculture.

Insight into the effect of ammonia doping on the methane jet flame - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Samuel Daniel; Wang Du; Ahmed E. Mansy; Kai-Ru Jin; Zhen-Yu Tian (Fuel, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incorporating Nondiet and Weight-Neutral Principles in a University Dietetics Curriculum - Nicholas Slagel; Daniel B. Hall; Yu Wang; Dawn Clifford; Cristen Harris; Jeffrey Hunger; Zoe Duran; Katelyn Crawley; Emma Laing (Journal of Nutrition Education and Behavior, 2025)

Unraveling structure–activity–acidity relationships in transition metal-modified ZSM-5 catalysts for complete propane oxidation - Samuel Daniel; Hannington Nevin Otieno; Aqsa Liaqat; Jia-Ying Liu; Cedric Karel Fonzeu Monguen; Zhen-Yu Tian (Journal of Environmental Chemical Engineering, 2025)

Unravelling sources of fecal pollution in oligotrophic mountain waters: Integrating Escherichia coli enumeration, microbial source tracking, and eDNA analysis - Sharon Maes; Martin Andersson-Li; Jessica Sjöstedt; Jon Hildahl; Daniel Yu; Norman Neumann; Monica Odlare; Anders Jonsson (Environmental Monitoring and Assessment, 2025)
Aquatic ecosystems in mountainous regions are crucial for fulfilling natural and anthropogenic water demands around the world. This study integrates Escherichia coli ( E. coli ) enumeration, microbial source tracking (MST), and environmental DNA (eDNA) analysis to identify sources of fecal contamination in oligotrophic mountain waters. Conducted in an area with intense tourism and traditional reindeer herding, this research addresses the urgent need to identify fecal pollution sources to safeguard the water quality of these vital ecosystems. Our study reveals that E. coli levels vary significantly across different locations and times, suggesting varied sources of contamination from humans, wildlife, and livestock animals. MST techniques, alongside eDNA analysis, provided insights into the complex patterns of fecal pollution, allowing for the distinction between human and animal contributions to water contamination. Our findings highlight the importance of combining various analytical methods to track fecal pollution sources effectively, and to develop targeted strategies for water quality management.

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

A new method for mechanical identification of unstable sliding rock - Yan Du; Hong-da Zhang; Mo-wen Xie; Yu-jing Jiang; Santos Daniel Chicas; Jing-nan Liu (Bulletin of Engineering Geology and the Environment, 2025)

Vulnerability and psychosocial impacts of extreme weather events among young people in Australia - Myriam Ziou; Daniel Z.Q. Gan; Bronwyn Boon; Shu Mei Teo; Jana M. Menssink; Wenhua Yu; Catherine L. Smith; Rebecca Patrick; Hasini Gunasiri; Nicholas J. Fava; David G. Baker; Vivienne Browne; et al. (Environmental Research, 2025)

Achieving optimised oxygen evolution reaction performance by tailoring NiFeMn layer double hydroxide composites - Laura J. Titheridge; Chang Wu; Shailendra Kumar Sharma; Campbell Tiffin; Daniel Holland; Yu Mao; Ziyun Wang; Geoffrey I.N. Waterhouse; Jiayang Li; Aaron T. Marshall (Chemical Engineering Journal, 2025)

Utility of the B/Ga salinity proxy in carbonate and marly sediments - Wei Wei; Thomas J. Algeo; David Meyer; Jiangsi Liu; Katherine N. Snihur; Cody Lazowski; Zhiquan Li; Daniel S. Alessi; Kurt O. Konhauser; Yuansheng Du; Wenchao Yu (Chemical Geology, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Attractive performance Cr-Co/ZSM-5 catalysts for the oxidative dehydrogenation of propane with carbon dioxide - Hannington Nevin Otieno; Samuel Daniel; Christiana Dupe Adegbesan; Bipro Gain; Jia-Ying Liu; Zhen-Yu Tian (Journal of Environmental Chemical Engineering, 2025)

Exploring Camellia oleifera Abel seed cake as sustainable source of protein for food applications: A review - Abel Wend-Soo Zongo; Chengyu Jin; Ningxiang Yu; Hongcai Cheng; Mahmoud Youssef; Daniel Zogona; Xiaohua Nie; Yuanchao Lu; Qin Ye; Xianghe Meng (Food Chemistry, 2025)

Catalytic production of aviation jet biofuels from biomass: a review - Ahmed E. Mansy; Samuel Daniel; Cedric Karel Fonzeu Monguen; Hao Wang; Ahmed I. Osman; Zhen-Yu Tian (Environmental Chemistry Letters, 2025)
The aviation sector is a major emitter of fossil fuel-derived carbon dioxide contributing to global warming. For instance, jet fuel consumed by the aviation industry is 1.5–1.7 billion barrels per year, resulting in 705 million metric tons of carbon dioxide emissions. Aircraft manufacturers have set ambitious goals, aiming for carbon-free growth post-2020 and a 50% reduction in greenhouse gas emissions by 2030. This issue can be solved by replacing fossil fuels with biofuels produced from modern biomass, thus meeting the carbon neutral objective. Here, we review the technologies to convert biomass into jet biofuel with focus on reactants, catalysts, and the chemistry of combustion. Reactants include alcohols, oil, esters, fatty acids, gas and sugars. Catalysts include Fischer–Tropsch catalysts, palladium, platinum, ruthenium, nickel, and molybdenum. The utilization of jet biofuels could potentially reduce greenhouse gas emissions by up to 80%. We also discuss economic implications.

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Adsorptive immobilization of cadmium and lead using unmodified and modified biochar: A review of the advances, synthesis, efficiency and mechanisms - Rong Qian; Kunru Yu; Nanyang Chen; Ronghua Li; Kuok Ho Daniel Tang (Chemosphere, 2025)

Effect of carbonation on transport properties of cementitious materials under different environmental conditions: A pore-scale modelling - Liang-yu Tong; Qing-feng Liu; Xiang Xu; Qing Xiang Xiong; Daniel C.W. Tsang (Journal of Cleaner Production, 2025)

Mechanisms underpinning microplastic effects on the natural climate solutions of wetland ecosystems - Michael Opoku Adomako; Ling Jin; Changchao Li; Jian Liu; Daniel Adu; Vivian Isabella Seshie; Fei-Hai Yu (Science of The Total Environment, 2024)

Experimental study of tsunami-bores impact on the elastic emerged plate - Daniel Bara Padang Allo; Yu Hsiao; Shih-Chun Hsiao (Ocean Engineering, 2024)

Large river expansion and global cooling controlled the Plio-Pleistocene weathering intensity records in East Asian margin - Fangliang Li; Shouye Yang; Daniel O. Breecker; Yulong Guo; Evan J. Ramos; Xiangtong Huang; Kai Deng; Jimin Yu; Sanzhong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Functional compounds of Torreya grandis nuts and their processing byproducts: Extraction process, health benefits, and food applications – A comprehensive review - Abel Wend-Soo Zongo; Chengyu Jin; Guijie Hao; Ningxiang Yu; Daniel Zogona; Xiaohua Nie; Yuanchao Lu; Qin Ye; Xianghe Meng (Food Research International, 2024)

Effects of desiccation and low temperature storage on oak (Quercus Sp) pollen - Daniel Ballesteros; Jose L. Canón-Prieto; Hugh W. Pritchard; Yu Tu; Hongying Chen; Raquel Folgado; Max Winkeljohn; Valerie C. Pence (Cryobiology, 2024)

Multi-omics analysis unravels the underlying mechanisms of the escape response of the common strain black carp (Cyprinus carpio var. baisenensis) - Yuanfeng Xu; Ping Dong; Daniel Yohannes Sewo; Shengyan Su; Jianlin Li; Wenrong Feng; Yu Liao; Yongkai Tang (Aquaculture International, 2024)

Incidence of contrast-induced neurotoxicity following endovascular treatment of unruptured intracranial aneurysms: a single-centre cohort study - Frederick P. Mariajoseph; Leon T. Lai; Justin Moore; Ronil V. Chandra; Tony Goldschlager; Adrian Praeger; Daniel Yu; Lee-Anne Slater (Acta Neurologica Belgica, 2024)
Background Contrast-induced neurotoxicity (CIN) is a recognised complication of endovascular procedures and has been increasingly observed in recent years. Amongst other clinical gaps, the precise incidence of CIN is unclear, particularly following intracranial interventional procedures. Methods A retrospective study of consecutive patients undergoing elective endovascular treatment of unruptured intracranial aneurysms (UIAs) was performed. Patients with previously ruptured aneurysms were excluded. The primary aim of this study was to determine the incidence of CIN following endovascular UIA treatment. Our secondary aim was to isolate potential predictive factors for developing CIN. Results From 2017 to 2023, a total of 158 patients underwent endovascular UIA treatment, with a median age of 64 years (IQR: 54–72), and 70.3% of female sex. Over the study period, the crude incidence of CIN was 2.5% (95% CI: 0.7 – 6.4%). The most common clinical manifestation of CIN was confusion (75%) and seizures (50%). Statistical analysis was conducted, and prolonged procedural duration was found be significantly associated with developing CIN (OR 12.55; p = 0.030). Conclusion Clinicians should be aware of the risk of CIN following endovascular neurointervention, particularly following technically challenging cases resulting in prolonged procedural time.

Phthalates on indoor surfaces and associated exposure via surface touch behavior: Observation in university dormitories and its implications - Fangzhou Yuan; Yu Sun; Na Li; Jianping Cao; Nan Zhang; Daniel Mmereki; Zhonghua Wei; Rui Chen; Jinyu Zhou; Yousheng Xu; Zhongming Bu (Building and Environment, 2024)

Synergistic effect of elevated CO2 and straw amendment on N2O emissions from a rice–wheat cropping system - Shengji Yan; Yunlong Liu; Daniel Revillini; Manuel Delgado-Baquerizo; Kees Jan van Groenigen; Ziyin Shang; Xin Zhang; Haoyu Qian; Yu Jiang; Aixing Deng; Pete Smith; Yanfeng Ding; et al. (Biology and Fertility of Soils, 2024)

Root traits regulate the capacity of the rhizosphere to support multiple ecosystem services under intercropping and phosphorus fertilization - Dongxue Tao; Yingzhi Gao; Daniel Revillini; An Yan; Guiyao Zhou; Clifford S. Swanson; Qiang He; Huimin Ma; Xiaoqian Yu; Manuel Delgado-Baquerizo (Agriculture, Ecosystems & Environment, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Applying seismic sedimentology to characterize the architecture of a fan delta complex: Triassic Baikouquan formation, Mahu Sag, Junggar Basin, western China - Zhichao Yu; Detian Yan; Guoxiang Zhao; Shicheng Yu; Caspar Daniel Adenutsi (Marine and Petroleum Geology, 2024)

Modeling the risk of aquatic species invasion spread through boater movements and river connections - Amy C. Kinsley; Szu‐Yu Zoe Kao; Eva A. Enns; Luis E. Escobar; Huijie Qiao; Nicholas Snellgrove; Ulirich Muellner; Petra Muellner; Ranjan Muthukrishnan; Meggan E. Craft; Daniel J. Larkin; Nicholas B. D. Phelps (Conservation Biology, 2024)
Aquatic invasive species (AIS) are one of the greatest threats to the functioning of aquatic ecosystems worldwide. Once an invasive species has been introduced to a new region, many governments develop management strategies to reduce further spread. Nevertheless, managing AIS in a new region is challenging because of the vast areas that need protection and limited resources. Spatial heterogeneity in invasion risk is driven by environmental suitability and propagule pressure, which can be used to prioritize locations for surveillance and intervention activities. To better understand invasion risk across aquatic landscapes, we developed a simulation model to estimate the likelihood of a waterbody becoming invaded with an AIS. The model included waterbodies connected via a multilayer network that included boater movements and hydrological connections. In a case study of Minnesota, we used zebra mussels ( Dreissena polymorpha ) and starry stonewort ( Nitellopsis obtusa ) as model species. We simulated the impacts of management scenarios developed by stakeholders and created a decision‐support tool available through an online application provided as part of the AIS Explorer dashboard. Our baseline model revealed that 89% of new zebra mussel invasions and 84% of new starry stonewort invasions occurred through boater movements, establishing it as a primary pathway of spread and offering insights beyond risk estimates generated by traditional environmental suitability models alone. Our results highlight the critical role of interventions applied to boater movements to reduce AIS dispersal.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Significant reductions of urban daytime ozone by extremely high concentration NOX from ship’s emissions: A case study - Zhe Song; Shaocai Yu; Xue Chen; Mengying Li; Pengfei Li; Ke Hu; Shengwen Liang; Jianmin Chen; Daniel Rosenfeld; John H. Seinfeld (Atmospheric Pollution Research, 2024)

A polyfunctionalized carbon framework composite for efficient decontamination of Cr(VI) and polycyclic aromatic nitrides from acidic wastewater - Weilong Wu; Han Zhang; Rong Qian; Kunru Yu; Ronghua Li; Kuok Ho Daniel Tang; Xuan Wu; Zhiqiang Guo; Cong Shao; Feixue Yue; Zengqiang Zhang (Environmental Science and Pollution Research, 2024)

Distribution and spatial variation of volatile methylsiloxanes in surface water and wastewater from the Yangtze River Basin, China - Yimeng Zhang; Ge Yin; G. Daniel Sheng; Zhenyang Yu; Daqiang Yin (Science of The Total Environment, 2024)

Unraveling the nexus: China's economic policy uncertainty and carbon emission efficiency through advanced multivariate quantile-on-quantile regression analysis - Yang Yu; Xin Jian; Hongxiang Wang; Atif Jahanger; Daniel Balsalobre-Lorente (Energy Policy, 2024)

Optimizing cultivation strategies and scaling up for fucoxanthin production using Pavlova sp. - Chun-Yen Chen; Ping-Yung Liu; Yu-Han Chang; Dillirani Nagarajan; Mary Joy D. Latagan; Mark Daniel G. de Luna; Jih-Heng Chen; Jo-Shu Chang (Bioresource Technology, 2024)

Unraveling the influence of CO2 and Ce loading over ZSM-5 for oxidative dehydrogenation of propane - Samuel Daniel; Cedric Karel Fonzeu Monguen; Zhen-Yu Tian (Chemical Engineering Journal, 2024)

Hornblendites as a record of differentiation, metasomatism and magma fertility in arc crust - Ren-Zhi Zhu; Daniel J. Smith; Fangyue Wang; Jiang-Feng Qin; Chao Zhang; Shaowei Zhao; Min Liu; Fangyi Zhang; Yu Zhu; Shao-Cong Lai (Chemical Geology, 2024)

Spatial Signatures of Biological Soil Crusts and Community Level Self-organization in Drylands - Daniel Kozar; Bettina Weber; Yu Zhang; Xiaoli Dong (Ecosystems, 2024)

Precipitation uncertainty estimation and rainfall-runoff model calibration using iterative ensemble smoothers - Davide Zoccatelli; Daniel B. Wright; Jeremy T. White; Michael N. Fienen; Guo Yu (Advances in Water Resources, 2024)

Potential synergy of microplastics and nitrogen enrichment on plant holobionts in wetland ecosystems - Michael Opoku Adomako; Jing Wu; Ying Lu; Daniel Adu; Vivian Isabella Seshie; Fei-Hai Yu (Science of The Total Environment, 2024)

Upwelling-driven biogenic silica accumulation in the Yangtze Sea, South China during Late Ordovician to Early Silurian time: A possible link with the global climatic transitions - Bowen Zan; Chuanlong Mou; Gary G. Lash; Qiyu Wang; Xiuqing Wang; Daniel Paul Le Heron; Jiaxin Yan; Zhifeng Zhang; Qian Hou; Yu Xia; Shengyang Yao (Sedimentary Geology, 2024)

Insight into the availability and desorption kinetics of Se and Cd in naturally-rich soils using diffusive gradients in thin-films technique - Chao Zhang; Dong-Xing Guan; Yi-Fan Jiang; Daniel Menezes-Blackburn; Tao Yu; Zhongfang Yang; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Large contributions of emission reductions and meteorological conditions to the abatement of PM2.5 in Beijing during the 24th Winter Olympic Games in 2022 - Yaping Jiang; Shaocai Yu; Xue Chen; Yibo Zhang; Mengying Li; Zhen Li; Zhe Song; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Journal of Environmental Sciences, 2024)

Au-loaded ZIF-8 derived porous carbon with improved photothermal catalysis ability from interfacial heating instead of hot-electrons - Hanhan Lv; Daniel K. Macharia; Zixiao Liu; Lisha Zhang; Chiyan Yu; Chihao Lu; Huansheng Liu; Yumei Zhang; Zhigang Chen (Chemical Engineering Journal, 2024)

Unrecognized pollution by inorganic condensable particulate matter in the atmosphere - Mengying Li; Shaocai Yu; Pengfei Li; Xue Chen; Zhe Song; Weiping Liu; Xiaoye Zhang; Meigen Zhang; Yele Sun; Zirui Liu; Jingkun Jiang; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2024)

Legume versus non-legume foliar litter decomposition in regularly burned loblolly pine forests - J. Brian Stogner; Daniel B. Hall; Mengyun Yu; Joseph J. Hendricks (Forest Ecology and Management, 2024)

XAS and DFT investigation of atomically dispersed Cu/Co alloyed Pt local structures under selective hydrogenation of acetylene to ethylene - Olumide Bolarinwa Ayodele; Toyin Daniel Shittu; Olayinka S. Togunwa; Dan Yu; Zhen-Yu Tian (Chemical Engineering Journal, 2024)

Parentage influence on gene expression under acidification revealed through single‐embryo sequencing - Cheuk Wang Fung; Kin Yung Chau; Daniel Chun Sang Tong; Claire Knox; Sindy Sing Ting Tam; Sin Yen Tan; Danson Shek Chun Loi; Ziuwin Leung; Ying Xu; Yi Lan; Pei‐Yuan Qian; Kit Yu Karen Chan; et al. (Molecular Ecology, 2023)
The dissolution of anthropogenic carbon dioxide (CO 2 ) in seawater has altered its carbonate chemistry in the process of ocean acidification (OA). OA affects the viability of marine species. In particular, calcifying organisms and their early planktonic larval stages are considered vulnerable. These organisms often utilize energy reserves for metabolism rather than growth and calcification as supported by bulk RNA‐sequencing (RNA‐seq) experiments. Yet, transcriptomic profiling of a bulk sample reflects the average gene expression of the population, neglecting the variations between individuals, which forms the basis for natural selection. Here, we used single‐embryo RNA‐seq on larval sea urchin Heliocidaris crassispina , which is a commercially and ecologically valuable species in East Asia, to document gene expression changes to OA at an individual and family level. Three paternal half‐sibs groups were fertilized and exposed to 3 pH conditions (ambient pH 8.0, 7.7 and 7.4) for 12 h prior to sequencing and oxygen consumption assay. The resulting transcriptomic profile of all embryos can be distinguished into four clusters, with differences in gene expressions that govern biomineralization, cell differentiation and patterning, as well as metabolism. While these responses were influenced by pH conditions, the male identities also had an effect. Specifically, a regression model and goodness of fit tests indicated a significant interaction between sire and pH on the probability of embryo membership in different clusters of gene expression. The single‐embryo RNA‐seq approach is promising in climate stressor research because not only does it highlight potential impacts before phenotypic changes were observed, but it also highlights variations between individuals and lineages, thus enabling a better determination of evolutionary potential.

Risk Level Assessment of Typhoon Hazard Based on Loss Utility - Guilin Liu; Bokai Yang; Xiuxiu Nong; Yi Kou; Fang Wu; Daniel Zhao; Pubing Yu (Journal of Marine Science and Engineering, 2023)
In the context of climate change with frequent natural disasters, disaster risk assessment can provide great help for related risk decision-making. Based on the theory of loss expectation, this paper presents a quantitative method to assess typhoon disaster risk. Among them, the probability of typhoon occurrence is calculated by fitting the optimal structure function of the sample to the joint distribution of wave height, water increment and wind speed. Then, the loss expectation is expressed as the product of typhoon occurrence probability and loss utility, which is used to quantify the loss result of a typhoon disaster. Using the loss utility theory, the risk grade chart is drawn with the direct economic loss rate and the proportion of the affected population as indicators. The results show that the absolute loss value considering the loss utility is slightly higher than the loss value of the quantitative algorithm by 2% to 25%, indicating that the new model reflects the social group’s aversion to typhoon disaster risk. As can be seen from the risk level zoning map, the highest combined risk level typhoons are Prapiroon 0606 and Chanthu 1003, with a risk level of Category 5. The typhoon comprehensive risk level before 2011 was ≥3, and the typhoon comprehensive risk level from 2012 to 2015 was ≤3. The evaluation model has certain feasibility and practicability, and the results can provide a basis and reference for typhoon risk assessment and decision-making.

Impact of architectural design strategies on the indoor natural ventilation of public residential buildings in Singapore - Ji-Yu Deng; Nyuk Hien Wong; Daniel Jun Chung Hii; Zhongqi Yu; Erna Tan; Meng Zhen; Shanshan Tong (Urban Climate, 2023)

Recycling of a post-industrial printed multilayer plastic film containing polyurethane inks by solvent-targeted recovery and precipitation - Kevin L. Sánchez-Rivera; Aurora del Carmen Munguía-López; Panzheng Zhou; Victor S. Cecon; Jiuling Yu; Kevin Nelson; Daniel Miller; Steve Grey; Zhuo Xu; Ezra Bar-Ziv; Keith L. Vorst; Greg W. Curtzwiler; et al. (Resources, Conservation and Recycling, 2023)

Identification and characterisation of MdUGT78T2 as a galactosyltransferase with dual activity on flavonol and anthocyanidin substrates in red-skinned apple fruit (Malus domestica L.) - Daniel Clayton-Cuch; Daniel McDougal; Julian G. Schwerdt; Long Yu; Neil Shirley; David Bradley; John B. Bruning; Christine Böttcher; Vincent Bulone (Food Chemistry, 2023)

Controlled synthesis of Cu-Cr double-layer thin films for oxidative dehydrogenation of propane at low temperature - Cedric Karel Fonzeu Monguen; Samuel Daniel; Zhen-Yu Tian (Chemical Engineering Journal, 2023)

Anthocitrus: evaluation of anthocyanin accumulating “Mexican” lime fruits produced by overexpressing the Ruby transcription factor gene from Citrus sinensis “Moro” - Manjul Dutt; Lamiaa M. Mahmoud; Kyle C. Weber; Aditi Satpute; Daniel Stanton; Wenming Qiu; Juliana M. Soares; Laura Reuss; Yu Wang; Jude W. Grosser; Nabil Killiny (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Intra-host mutation rate of acute SARS-CoV-2 infection during the initial pandemic wave - Kim El-Haddad; Thamali M. Adhikari; Zheng Jin Tu; Yu-Wei Cheng; Xiaoyi Leng; Xiangyi Zhang; Daniel Rhoads; Jennifer S. Ko; Sarah Worley; Jing Li; Brian P. Rubin; Frank P. Esper (Virus Genes, 2023)

Coupled effects of elevated CO2 and biochar on microbial communities of vegetated soil - Charles Wang Wai Ng; Jia Xin Liao; Sze Yu Lau; Pui San So; Billy Chi Hang Hau; Daniel Peprah-manu (Journal of Environmental Management, 2023)

Comprehensive magnetic analysis of the tephras in Middle-Late Pleistocene loess records of Serbia, and implications for tephra identification, correlation and loess chronology - Namier Namier; Qingzhen Hao; Xinbo Gao; Yu Fu; Slobodan B. Marković; Ulrich Hambach; Daniel Veres; Joseph A. Mason; Yang Song; Chenglong Deng; Milivoj B. Gavrilov; Rastko Marković; et al. (Quaternary Science Reviews, 2023)

Distribution Characteristics and Influencing Factors of Bio-elements in the Human Hair of Uyghur Communities in an Oasis Area of Xinjiang, China - Muyesaier Tudi; Fengqing Jiang; Li Wang; Hairong Li; Shuangmei Tong; Jiangping Yu; Min Meng; Lin sheng Yang; Muhammad Ubaid Ali; Qiming Jimmy Yu; Huada Daniel Ruan (Biological Trace Element Research, 2023)

Leaching characteristics and potential risk of heavy metals from drip irrigation pipes and mulch substrate in agricultural ecosystems - Muyesaier Tudi; Linsheng Yang; Jiangping Yu; Binggan Wei; Yuan Xue; Fang Wang; Linfeng Li; Qiming Jimmy Yu; Huada Daniel Ruan; Qin Li; Ross Sadler; Des Connell (Science of The Total Environment, 2023)

The effect of modifier adding sequence on physical-chemical property and adsorption ability of Inorganic-Organic Montmorillonite (IOMMt) - Jiajun Chen; Jianzun Lu; Sabrina Yanan Jiang; Chiu Hong Lee; Yu Li; Huada Daniel Ruan (Journal of Environmental Chemical Engineering, 2023)

Tailored synthesized Pt/ZSM-5 catalysts with excellent water vapor stability for low temperature oxidation of CO and C3H6 - Samuel Daniel; Cedric Karel Fonzeu Monguen; Olumide Bolarinwa Ayodele; Zhen-Yu Tian (Journal of Environmental Chemical Engineering, 2023)

Uncertainty quantification of inflow on passive scalar dispersion in an urban environment - Bharathi Boppana; Vinh-Tan Nguyen; Daniel J. Wise; Jason Yu Chuan Leong (Environmental Fluid Mechanics, 2023)

Candida species causing fungal keratitis: molecular identification, antifungal susceptibility, biofilm formation, and clinical aspects - Fernanda M. Bezerra; Talita T. Rocchetti; Soraia L. Lima; Maria Cecília Z. Yu; Daniel A. da Matta; Ana Luisa Höfling-Lima; Analy S. A. Melo; Lauro A. de Oliveira (Brazilian Journal of Microbiology, 2023)

Across‐model spread and shrinking in predicting peatland carbon dynamics under global change - Enqing Hou; Shuang Ma; Yuanyuan Huang; Yu Zhou; Hyung‐Sub Kim; Efrén López‐Blanco; Lifen Jiang; Jianyang Xia; Feng Tao; Christopher Williams; Mathew Williams; Daniel Ricciuto; et al. (Global Change Biology, 2023)
Large across‐model spread in simulating land carbon (C) dynamics has been ubiquitously demonstrated in model intercomparison projects (MIPs), and became a major impediment in advancing climate change prediction. Thus, it is imperative to identify underlying sources of the spread. Here, we used a novel matrix approach to analytically pin down the sources of across‐model spread in transient peatland C dynamics in response to a factorial combination of two atmospheric CO 2 levels and five temperature levels. We developed a matrix‐based MIP by converting the C cycle module of eight land models (i.e., TEM, CENTURY4, DALEC2, TECO, FBDC, CASA, CLM4.5 and ORCHIDEE) into eight matrix models. While the model average of ecosystem C storage was comparable to the measurement, the simulation differed largely among models, mainly due to inter‐model difference in baseline C residence time. Models generally overestimated net ecosystem production (NEP), with a large spread that was mainly attributed to inter‐model difference in environmental scalar. Based on the sources of spreads identified, we sequentially standardized model parameters to shrink simulated ecosystem C storage and NEP to almost none. Models generally captured the observed negative response of NEP to warming, but differed largely in the magnitude of response, due to differences in baseline C residence time and temperature sensitivity of decomposition. While there was a lack of response of NEP to elevated CO 2 (eCO 2 ) concentrations in the measurements, simulated NEP responded positively to eCO 2 concentrations in most models, due to the positive responses of simulated net primary production. Our study used one case study in Minnesota peatland to demonstrate that the sources of across‐model spreads in simulating transient C dynamics can be precisely traced to model structures and parameters, regardless of their complexity, given the protocol that all the matrix models were driven by the same gross primary production and environmental variables.

Widespread missing super-emitters of nitrogen oxides across China inferred from year-round satellite observations - Yuqing Pan; Lei Duan; Mingqi Li; Pinqing Song; Nan Xv; Jing Liu; Yifei Le; Mengying Li; Cui Wang; Shaocai Yu; Daniel Rosenfeld; John H. Seinfeld; et al. (Science of The Total Environment, 2023)

Uncertainty analysis for the calculation of marine environmental design parameters in the South China Sea - Guilin Liu; Xinsheng Zhou; Yi Kou; Fang Wu; Daniel Zhao; Yu Xu (Journal of Oceanology and Limnology, 2023)

Assessment of typhoon storm surge disaster scale based on expansion model - Guilin Liu; Xiuxiu Nong; Yi Kou; Fang Wu; Daniel Zhao; Zongbing Yu (Journal of Oceanology and Limnology, 2023)

Airborne microplastics: Occurrence, sources, fate, risks and mitigation - Xinran Zhao; Yupeng Zhou; Chenzhe Liang; Jianchen Song; Siyun Yu; Gengxuan Liao; Peiyan Zou; Kuok Ho Daniel Tang; Chenmiao Wu (Science of The Total Environment, 2023)

Aerosolized aqueous dust extracts collected near a drying lake trigger acute neutrophilic pulmonary inflammation reminiscent of microbial innate immune ligands - Trevor A. Biddle; Keziyah Yisrael; Ryan Drover; Qi Li; Mia R. Maltz; Talyssa M. Topacio; Jasmine Yu; Diana Del Castillo; Daniel Gonzales; Hannah L. Freund; Mark P. Swenson; Malia L. Shapiro; et al. (Science of The Total Environment, 2023)

Genesis of authigenic clay minerals and their impacts on reservoir quality in tight conglomerate reservoirs of the Triassic Baikouquan formation in the Mahu Sag, Junggar Basin, Western China - Zhichao Yu; Zhizhang Wang; Caspar Daniel Adenutsi (Marine and Petroleum Geology, 2023)

Blue carbon science, management and policy across a tropical urban landscape - Daniel A. Friess; Yasmine M. Gatt; Tze Kwan Fung; Jahson B. Alemu; Natasha Bhatia; Rebecca Case; Siew Chin Chua; Danwei Huang; Valerie Kwan; Kiah Eng Lim; Yudhishthra Nathan; Yan Xiang Ow; et al. (Landscape and Urban Planning, 2023)

Multiple-functionalized biochar affects rice yield and quality via regulating arsenic and lead redistribution and bacterial community structure in soils under different hydrological conditions - Xing Yang; Zhinan Dai; Chengjun Ge; Huamei Yu; Nanthi Bolan; Daniel C.W. Tsang; Hocheol Song; Deyi Hou; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

Seasonal variability of phytoplankton community response to thermal discharge from nuclear power plant in temperate coastal area - Jingjing Zhang; Yibin Wang; Daniel Ottmann; Peng Cao; Jisong Yang; Junbao Yu; Zhenbo Lv (Environmental Pollution, 2023)

High-performance post-treatment-free PEDOT based thermoelectric with the establishment of long-range ordered conductive paths - Xin Li; Zhenhang He; Zhen Liu; Yu Chen; Zekun Zhou; Guixiang Chen; Weiheng Qi; Daniel Rauber; Christopher W. M. Kay; Peng Zhang (Chemical Engineering Journal, 2023)

An Early Cretaceous gold mineralization event in the Triassic West Qinling orogen revealed from U-Pb titanite dating of the Ma’anqiao gold deposit - Chongguo He; Jianwei Li; Daniel J. Kontak; Xiaoye Jin; Yafei Wu; Hao Hu; Bo Zu; Xueling Yu; Shaorui Zhao; Shiguang Du; Yunlong Zhu; Huan Tao (Science China Earth Sciences, 2023)

Porphyry-epithermal Cu-Mo-Au–Ag mineralization in the Nakhodka ore field, Baimka Trend, Chukotka, Russia: a geological, mineralogical, and geochemical perspective - Andrey F. Chitalin; Ivan A. Baksheev; Yurii N. Nikolaev; Ekaterina V. Nagornaya; Yuliya N. Khabibullina; Irina Yu. Nikolaeva; Ildar A. Kalko; Daniel Müller (Mineralium Deposita, 2023)

Facilitation of non-indigenous ascidian by marine eco-engineering interventions at an urban site - Nina Schaefer; Francisco Sedano; Melanie J. Bishop; Kate Dunn; M. Hank Haeusler; K. Daniel Yu; Yannis Zavoleas; Katherine A. Dafforn (Biofouling, 2023)

Advancing freshwater ecological forecasts: Harmful algal blooms in Lake Erie - Donald Scavia; Yu-Chen Wang; Daniel R. Obenour (Science of The Total Environment, 2023)

Effects of spatially heterogeneous lakeside development on nearshore biotic communities in a large, deep, oligotrophic lake - Michael F. Meyer; Ted Ozersky; Kara H. Woo; Kirill Shchapov; Aaron W. E. Galloway; Julie B. Schram; Emma J. Rosi; Daniel D. Snow; Maxim A. Timofeyev; Dmitry Yu. Karnaukhov; Matthew R. Brousil; Stephanie E. Hampton (Limnology and Oceanography, 2022)
Sewage released from lakeside development can reshape ecological communities. Nearshore periphyton can rapidly assimilate sewage‐associated nutrients, leading to increases of filamentous algal abundance, thus altering both food abundance and quality for grazers. In Lake Baikal, a large, ultra‐oligotrophic, remote lake in Siberia, filamentous algal abundance has increased near lakeside developments, and localized sewage input is the suspected cause. These shifts are of particular interest in Lake Baikal, where endemic littoral biodiversity is high, lakeside settlements are mostly small, tourism is relatively high (~1.2 million visitors annually), and settlements are separated by large tracts of undisturbed shoreline, enabling investigation of heterogeneity and gradients of disturbance. We surveyed sites along 40 km of Baikal's southwestern shore for sewage indicators—pharmaceuticals and personal care products (PPCPs) and microplastics—as well as periphyton and macroinvertebrate abundance and indicators of food web structure (stable isotopes and fatty acids). Summed PPCP concentrations were spatially related to lakeside development. As predicted, lakeside development was associated with more filamentous algae and lower abundance of sewage‐sensitive mollusks. Periphyton and macroinvertebrate stable isotopes and essential fatty acids suggested that food web structure otherwise remained similar across sites; yet, the invariance of amphipod fatty acid composition, relative to periphyton, suggested that grazers adjust behavior or metabolism to compensate for different periphyton assemblages. Our results demonstrate that even low levels of human disturbance can result in spatial heterogeneity of nearshore ecological responses, with potential for changing trophic interactions that propagate through the food web.

Differential impacts of adult trees on offspring and non-offspring recruits in a subtropical forest - Fang Wang; Xiangcheng Mi; Lei Chen; Wubing Xu; Walter Durka; Nathan G. Swenson; Daniel J. Johnson; Samantha J. Worthy; Jianhua Xue; Yan Zhu; Bernhard Schmid; Yu Liang; et al. (Science China Life Sciences, 2022)

WASHC1 interacts with MCM2-7 complex to promote cell survival under replication stress - Yu Hong; He Sun; Xian Hong; Cai-Ping Yang; Daniel D. Billadeau; Tao Wang; Zhi-Hui Deng (Molecular Biology Reports, 2022)

Environmental monitoring and potential health risk assessment from Pymetrozine exposure among communities in typical rice-growing areas of China - Muyesaier Tudi; Li Wang; Huada Daniel Ruan; Shuangmei Tong; Albert Atabila; Ross Sadler; Qiming Jimmy Yu; Des Connell; Dung Tri Phung (Environmental Science and Pollution Research, 2022)

Variations in Hydraulic Conductivity of Montmorillonite in Dual-Cation Electrolyte Solutions - Jingyi Feng; Qi Yu; Anfei He; G. Daniel Sheng (Bulletin of Environmental Contamination and Toxicology, 2022)

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Local production, downward and regional transport aggravated surface ozone pollution during the historical orange-alert large-scale ozone episode in eastern China - Yibo Zhang; Shaocai Yu; Xue Chen; Zhen Li; Mengying Li; Zhe Song; Weiping Liu; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Environmental Chemistry Letters, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

COCH-related autosomal dominant nonsyndromic hearing loss: a phenotype–genotype study - Kyung Seok Oh; Daniel Walls; Sun Young Joo; Jung Ah Kim; Jee Eun Yoo; Young Ik Koh; Da Hye Kim; John Hoon Rim; Hye Ji Choi; Hye-Youn Kim; Seyoung Yu; Richard J. Smith; et al. (Human Genetics, 2022)

Chronic mild stress paradigm as a rat model of depression: facts, artifacts, and future perspectives - Tatyana Strekalova; Yanzhi Liu; Daniel Kiselev; Sharafuddin Khairuddin; Jennifer Lok Yu Chiu; Justin Lam; Ying-Shing Chan; Dmitrii Pavlov; Andrey Proshin; Klaus-Peter Lesch; Daniel C. Anthony; Lee Wei Lim (Psychopharmacology, 2022)
Rationale The chronic mild stress (CMS) paradigm was first described almost 40 years ago and has become a widely used model in the search for antidepressant drugs for major depression disorder (MDD). It has resulted in the publication of almost 1700 studies in rats alone. Under the original CMS procedure, the expression of an anhedonic response, a key symptom of depression, was seen as an essential feature of both the model and a depressive state. The prolonged exposure of rodents to unpredictable/uncontrollable mild stressors leads to a reduction in the intake of palatable liquids, behavioral despair, locomotor inhibition, anxiety-like changes, and vegetative (somatic) abnormalities. Many of the CMS studies do not report these patterns of behaviors, and they often fail to include consistent molecular, neuroanatomical, and physiological phenotypes of CMS-exposed animals. Objectives To critically review the CMS studies in rats so that conceptual and methodological flaws can be avoided in future studies. Results Analysis of the literature supports the validity of the CMS model and its impact on the field. However, further improvements could be achieved by (i) the stratification of animals into ‘resilient’ and ‘susceptible’ cohorts within the CMS animals, (ii) the use of more refined protocols in the sucrose test to mitigate physiological and physical artifacts, and (iii) the systematic evaluation of the non-specific effects of CMS and implementation of appropriate adjustments within the behavioral tests. Conclusions We propose methodological revisions and the use of more advanced behavioral tests to refine the rat CMS paradigm, which offers a valuable tool for developing new antidepressant medications.

Natural forests promote phosphorus retention in soil - Zhen Yu; Zhou Guoyi; Lei Liu; Stefano Manzoni; Philippe Ciais; Daniel Goll; Josep Peñuelas; Jordi Sardans; Wantong Wang; Jie Zhu; Lin Li; Junhua Yan; et al. (Global Change Biology, 2022)
Soil phosphorus (P) availability often limits plant productivity. Classical theories suggest that total P content declines at the temporal scale of pedogenesis, and ecosystems develop toward the efficient use of scarce P during succession. However, the trajectory of ecosystem P within shorter time scales of succession remains unclear. We analyzed changes to P pools at the early (I), middle (II), and late (III) stages of growth of plantation forests (PFs) and the successional stages of natural forests (NFs) at 1969 sites in China. We found significantly lower P contents at later growth stages compared to earlier ones in the PF ( p p

Large scale control of surface ozone by relative humidity observed during warm seasons in China - Mengying Li; Shaocai Yu; Xue Chen; Zhen Li; Yibo Zhang; Liqiang Wang; Weiping Liu; Pengfei Li; Eric Lichtfouse; Daniel Rosenfeld; John H. Seinfeld (Environmental Chemistry Letters, 2021)

Unintentional parasite conservation success: chewing lice recovered from Crested Ibis, Nipponia nippon, in breeding program facilities in Shaanxi, China - Daniel R.. Gustafsson; Chunpo Tian; Xiaoping Yu; Lulu Xu; Si Wu; Fasheng Zou (Biodiversity and Conservation, 2021)

Translocation versus ion trapping in the root uptake of 2,4-dichlorophenol by wheat seedlings - Qi Yu; Anfei He; Dongjin Shi; G. Daniel Sheng (Environmental Science and Pollution Research, 2021)

miR-181a Mediates Inflammatory Gene Expression After Intracerebral Hemorrhage: An Integrated Analysis of miRNA-seq and mRNA-seq in a Swine ICH Model - Kyle B. Walsh; Kip D. Zimmerman; Xiang Zhang; Stacie L. Demel; Yu Luo; Carl D. Langefeld; Eric Wohleb; Grant Schulert; Daniel Woo; Opeolu Adeoye (Journal of Molecular Neuroscience, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Special issue on contamination, remediation and health for pollutants in natural aquatic, soil, sediments and atmospheric environments - Kitae Baek; Daniel S. Alessi; Yu Bon Man; Eilhann E. Kwon (Environmental Geochemistry and Health, 2021)

Bioaccumulation and translocation of trace elements in soil-irrigation water-wheat in arid agricultural areas of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Yunjiang Yu; Li Wang; Binggan Wei; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Ecotoxicology, 2021)

The bacterium Pseudomonas protegens antagonizes the microalga Chlamydomonas reinhardtii using a blend of toxins - Magdalena M. Rose; Daniel Scheer; Yu Hou; Vivien S. Hotter; Anna J. Komor; Prasad Aiyar; Kirstin Scherlach; Fredd Vergara; Qing Yan; Joyce E. Loper; Torsten Jakob; Nicole M. van Dam; et al. (Environmental Microbiology, 2021)
Summary The unicellular alga Chlamydomonas reinhardtii and the bacterium Pseudomonas protegens serve as a model to study the interactions between photosynthetic and heterotrophic microorganisms. P . protegens secretes the cyclic lipopeptide orfamide A that interferes with cytosolic Ca 2+ homeostasis in C . reinhardtii resulting in deflagellation of the algal cells. Here, we studied the roles of additional secondary metabolites secreted by P . protegens using individual compounds and co‐cultivation of algae with bacterial mutants. Rhizoxin S2, pyrrolnitrin, pyoluteorin, 2,4‐diacetylphloroglucinol (DAPG) and orfamide A all induce changes in cell morphology and inhibit the growth of C . reinhardtii . Rhizoxin S2 exerts the strongest growth inhibition, and its action depends on the spatial structure of the environment (agar versus liquid culture). Algal motility is unaffected by rhizoxin S2 and is most potently inhibited by orfamide A (IC 50 = 4.1 μM). Pyrrolnitrin and pyoluteorin both interfere with algal cytosolic Ca 2+ homeostasis and motility whereas high concentrations of DAPG immobilize C . reinhardtii without deflagellation or disturbance of Ca 2+ homeostasis. Co‐cultivation with a regulatory mutant of bacterial secondary metabolism (Δ gacA ) promotes algal growth under spatially structured conditions. Our results reveal how a single soil bacterium uses an arsenal of secreted antialgal compounds with complementary and partially overlapping activities.

Chemicals from lignocellulosic biomass: A critical comparison between biochemical, microwave and thermochemical conversion methods - Iris K. M. Yu; Huihui Chen; Felix Abeln; Hadiza Auta; Jiajun Fan; Vitaly L. Budarin; James H. Clark; Sophie Parsons; Christopher J. Chuck; Shicheng Zhang; Gang Luo; Daniel C.W Tsang (Critical Reviews in Environmental Science and Technology, 2021)

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Elevation Calculation of Bottom Deck Based on Stochastic Process and Compound Distribution - Guilin Liu; Chi Nie; Yi Kou; Yi Yang; Daniel Zhao; Fang Wu; Pubing Yu (Journal of Marine Science and Engineering, 2021)
In the design of offshore platforms, the height of the bottom deck directly affects the safety and engineering cost of the entire platform. It is a very important scale parameter in platform planning. The American Petroleum Institute (API) specification shows that the key to determining the height of the bottom deck lies in the wave height and calculation of the return level of the water increase. Based on the perspective of stochastic processes, this paper constructs a new distribution function model for joint parameter estimation of the marine environment. The new model uses a family of random variables to show the statistical characteristics of design wave height and water increase in both time and space, with extreme value expanded EED-I type distribution used as marginal distribution. The new model performs statistical analysis on the measured hydrological data of the Naozhou Station during the flood period from 1990 to 2016. The Gumbel–Copula structure function is used as the connection function, and the compound distribution model of the wave height and the water increase is used to obtain the joint return level of the wave height and the water increase and through which the bottom deck height of the area is calculated. The results show that the stochastic compound distribution improves the issue of the high design value caused by simple superposition of univariate return levels. The EED-I type distribution still has good stability under the condition of less measured data. Thus, under the premise of ensuring the safety of the offshore platform, less measured data can still be used to calculate the height of the bottom deck more accurately.

Global patterns and drivers of alpine plant species richness - Riccardo Testolin; Fabio Attorre; Peter Borchardt; Robert F. Brand; Helge Bruelheide; Milan Chytrý; Michele De Sanctis; Jiri Dolezal; Manfred Finckh; Sylvia Haider; Andreas Hemp; Ute Jandt; et al. (Global Ecology and Biogeography, 2021)
Aim Alpine ecosystems differ in area, macroenvironment and biogeographical history across the Earth, but the relationship between these factors and plant species richness is still unexplored. Here, we assess the global patterns of plant species richness in alpine ecosystems and their association with environmental, geographical and historical factors at regional and community scales. Location Global. Time period Data collected between 1923 and 2019. Major taxa studied Vascular plants. Methods We used a dataset representative of global alpine vegetation, consisting of 8,928 plots sampled within 26 ecoregions and six biogeographical realms, to estimate regional richness using sample‐based rarefaction and extrapolation. Then, we evaluated latitudinal patterns of regional and community richness with generalized additive models. Using environmental, geographical and historical predictors from global raster layers, we modelled regional and community richness in a mixed‐effect modelling framework. Results The latitudinal pattern of regional richness peaked around the equator and at mid‐latitudes, in response to current and past alpine area, isolation and the variation in soil pH among regions. At the community level, species richness peaked at mid‐latitudes of the Northern Hemisphere, despite a considerable within‐region variation. Community richness was related to macroclimate and historical predictors, with strong effects of other spatially structured factors. Main conclusions In contrast to the well‐known latitudinal diversity gradient, the alpine plant species richness of some temperate regions in Eurasia was comparable to that of hyperdiverse tropical ecosystems, such as the páramo. The species richness of these putative hotspot regions is explained mainly by the extent of alpine area and their glacial history, whereas community richness depends on local environmental factors. Our results highlight hotspots of species richness at mid‐latitudes, indicating that the diversity of alpine plants is linked to regional idiosyncrasies and to the historical prevalence of alpine ecosystems, rather than current macroclimatic gradients.

Variations of carbon allocation and turnover time across tropical forests - Hui Yang; Philippe Ciais; Yilong Wang; Yuanyuan Huang; Jean‐Pierre Wigneron; Ana Bastos; Jérôme Chave; Jinfeng Chang; Christopher E. Doughty; Lei Fan; Daniel Goll; Emilie Joetzjer; et al. (Global Ecology and Biogeography, 2021)
Aim The carbon sink in tropical forests is a highly uncertain component of the global carbon budget. An understanding of the processes controlling this sink requires better quantification of carbon allocation, stocks and turnover times. Location Tropical forests. Time period 2010–2017. Major taxa studied Tropical forest ecosystem. Methods We develop a novel data assimilation system using satellite‐based annual above‐ground biomass derived from L‐band vegetation optical depth with 25 km × 25 km grid spacing, together with leaf area, to constrain the 25 km × 25 km carbon allocation patterns of net primary productivity (NPP) into the wood, leaf and root pools, and their turnover times. Our average data‐driven estimates of these variables are broadly consistent with independent ground‐based estimates of NPP allocation and wood turnover from forest inventory plots. Results In tropical forest, on average, the NPP allocation into wood (0.30 ± 0.04) is significantly higher than that into leaves (0.24 ± 0.07). From the wet to dry tropics, forest NPP allocation into both wood and leaves declines slightly. The turnover times of forest leaf pools exhibit little spatial variation, whereas the turnover times of wood pools in Africa (median and interquartile range: years) are slightly longer than those in South America ( years) and Southeast Asia ( years). Our datasets reveal emergent trade‐offs across climatic and vegetation gradients between growth and life span/turnover for both wood and leaves. The spatial gradients of NPP allocation to wood/leaves are associated with canopy height, adjusted by climate condition and nutrient acquisition. The spatial gradients of wood and leaf turnover times are influenced mainly by climate and leaf characteristics. Main conclusions Our data‐driven estimates of carbon allocation and turnover times provide a basis for more detailed exploration of these mechanisms in field studies. This highlights that improved model representation of carbon allocation and turnover is necessary for more accurate prediction of future carbon dynamics.

Nickel ferrite nanoenabled graphene oxide (NiFe2O4@GO) as photoactive nanocomposites for water treatment - Allen Rhay B. Bayantong; Yu-Jen Shih; Cheng-Di Dong; Sergi Garcia-Segura; Mark Daniel G. de Luna (Environmental Science and Pollution Research, 2021)

Maximum July–September temperatures derived from tree‐ring densities on the western Loess Plateau, China - Huiming Song; Ruochen Mei; Yu Liu; Daniel Nievergelt; Anne Verstege; Paolo Cherubini; Ruoshi Liu; Changfeng Sun; Qiang Li; Ling Chen; Xueli Zeng; Junqin Guo (International Journal of Climatology, 2021)
Tree‐ring densitometric studies conducted in semi‐arid regions are exceedingly rare. In this study, we evaluate a new maximum latewood density chronology from a collection of Picea purpurea trees growing in semi‐arid northwestern China for climatic reconstruction purposes. We find statistically significant correlations between annual maximum density variations and July–September maximum temperatures over the 1957–2014 calibration period. Using a linear model to transfer the density variations to temperature estimates, we then reconstruct maximum summer temperatures from 1840 to 2014. Statistical analyses and verification tests demonstrate that the resulting transfer function is both reliable and stable. The reconstructed temperature series shows strong inter‐annual and decadal variability. Several extremely cool and warm years are apparent on an inter‐annual scale, while three extended cool periods and a warm period are observed on a decadal scale. In addition, the reconstructed temperature series exhibits a pattern synchronous with that of the Indian monsoon index, as well as a moderate relationship to volcanic eruptions. This densitometric study reveals typical climatic variation characteristics and provides useful data for deepening our understanding of climate history in the semi‐arid regions of China.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Key rules of life and the fading cryosphere: Impacts in alpine lakes and streams - James J. Elser; Chenxi Wu; Angélica L. González; Daniel H. Shain; Heidi J. Smith; Ruben Sommaruga; Craig E. Williamson; Janice Brahney; Scott Hotaling; Joseph Vanderwall; Jinlei Yu; Vladimir Aizen; et al. (Global Change Biology, 2020)
Alpine regions are changing rapidly due to loss of snow and ice in response to ongoing climate change. While studies have documented ecological responses in alpine lakes and streams to these changes, our ability to predict such outcomes is limited. We propose that the application of fundamental rules of life can help develop necessary predictive frameworks. We focus on four key rules of life and their interactions: the temperature dependence of biotic processes from enzymes to evolution; the wavelength dependence of the effects of solar radiation on biological and ecological processes; the ramifications of the non‐arbitrary elemental stoichiometry of life; and maximization of limiting resource use efficiency across scales. As the cryosphere melts and thaws, alpine lakes and streams will experience major changes in temperature regimes, absolute and relative inputs of solar radiation in ultraviolet and photosynthetically active radiation, and relative supplies of resources (e.g., carbon, nitrogen, and phosphorus), leading to nonlinear and interactive effects on particular biota, as well as on community and ecosystem properties. We propose that applying these key rules of life to cryosphere‐influenced ecosystems will reduce uncertainties about the impacts of global change and help develop an integrated global view of rapidly changing alpine environments. However, doing so will require intensive interdisciplinary collaboration and international cooperation. More broadly, the alpine cryosphere is an example of a system where improving our understanding of mechanistic underpinnings of living systems might transform our ability to predict and mitigate the impacts of ongoing global change across the daunting scope of diversity in Earth's biota and environments.

Noradrenergic circuits in the forebrain control affective responses to novelty - Daniel Lustberg; Rachel P. Tillage; Yu Bai; Molly Pruitt; L. Cameron Liles; David Weinshenker (Psychopharmacology, 2020)

Biorefinery-assisted soil management for enhancing food security - Iris K.M. Yu; Daniel C.W. Tsang; Deyi Hou (Journal of Soils and Sediments, 2020)

Guest Editorial to the Special Issue: Lessons Learned from post-2008 Wenchuan Earthquake Community Recovery - Robert Olshansky; Yu Xiao; Daniel Abramson (Natural Hazards, 2020)

Potentiated In Vitro Probiotic Activities of Lactobacillus fermentum LfQi6 Biofilm Biomass Versus Planktonic Culture - Eva Berkes; Yu-Hsien Liao; Daniel Neef; Michael Grandalski; Nicholas Monsul (Probiotics and Antimicrobial Proteins, 2020)

Roles of N-methyl-d-aspartate receptors and d-amino acids in cancer cell viability - Siqi Du; Yu-Sheng Sung; Michael Wey; Yadi Wang; Nagham Alatrash; Alain Berthod; Frederick M. MacDonnell; Daniel W. Armstrong (Molecular Biology Reports, 2020)

Unexpected rise of ozone in urban and rural areas, and sulfur dioxide in rural areas during the coronavirus city lockdown in Hangzhou, China: implications for air quality - Liqiang Wang; Mengying Li; Shaocai Yu; Xue Chen; Zhen Li; Yibo Zhang; Linhui Jiang; Yan Xia; Jiali Li; Weiping Liu; Pengfei Li; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2020)

Ultrastructural Characteristics of DHA-Induced Pyroptosis - Deron R. Herr; Ting Yu Amelia Yam; Wan Shun Daniel Tan; Sally Shuxian Koh; Wai Shiu Fred Wong; Wei-Yi Ong; Kanokporn Chayaburakul (NeuroMolecular Medicine, 2020)
Microglial cells are resident macrophages of the central nervous system (CNS) that respond to bioactive lipids such as docosahexaenoic acid (DHA). Low micromolar concentrations of DHA typically promote anti-inflammatory functions of microglia, but higher concentrations result in a form of pro-inflammatory programmed cell death known as pyroptosis. This study used scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to investigate the morphological characteristics of pyroptosis in BV-2 microglial cells following exposure to 200 µM DHA. Vehicle-treated cells are characterized by extended processes, spine-like projections or 0.4 to 5.2 µm in length, and numerous extracellular vesicles (EVs) tethered to the surface of the plasma membrane. In contrast to vehicle-treated cells, gross abnormalities are observed after treating cells with 200 µM DHA for 4 h. These include the appearance of numerous pits or pores of varying sizes across the cell surface, structural collapse and flattening of the cell shape. Moreover, EVs and spines were lost following DHA treatment, possibly due to release from the cell surface. The membrane pores appear after DHA treatment initially measured ~ 30 nm, consistent with the previously reported gasdermin D (GSDMD) pore complexes. Complete collapse of cytoplasmic organization and loss of nuclear envelope integrity were also observed in DHA-treated cells. These processes are morphologically distinct from the changes that occur during cisplatin-induced apoptosis, such as the appearance of apoptotic bodies and tightly packed organelles, and the maintenance of EVs and nuclear envelope integrity. Cumulatively, this study provides a systematic description of the ultrastructural characteristics of DHA-induced pyroptosis, including distinguishing features that differentiate this process from apoptosis.

Common source areas of air pollution vary with haze intensity in the Yangtze River Delta, China - Xue Chen; Shaocai Yu; Liqiang Wang; Zhen Li; Yibo Zhang; Mengying Li; Khalid Mehmood; Weiping Liu; Pengfei Li; Eric Lichtfouse; Daniel Rosenfeld; John H. Seinfeld (Environmental Chemistry Letters, 2020)

Media Reports of Unintentional Opioid Exposure of Public Safety First Responders in North America - Paul Alexander Herman; Daniel Saul Brenner; Stewart Dandorf; Stephanie Kemp; Breann Kroll; Joshua Trebach; Yu-Hsiang Hsieh; Andrew Ian Stolbach (Journal of Medical Toxicology, 2020)

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Vertical distribution of echinoid larvae in pH stratified water columns - Elizaldy A. Maboloc; Grant Batzel; Daniel Grünbaum; Kit Yu Karen Chan (Marine Biology, 2020)

Landscape-Level Consequences of Rising Sea-Level on Coastal Wetlands: Saltwater Intrusion Drives Displacement and Mortality in the Twenty-First Century - Mei Yu; Elsie Rivera-Ocasio; Tamara Heartsill-Scalley; Daniel Davila-Casanova; Neftalí Rios-López; Qiong Gao (Wetlands, 2019)

A key metabolic integrator, coenzyme A, modulates the activity of peroxiredoxin 5 via covalent modification - Jovana Baković; Bess Yi Kun Yu; Daniel Silva; Sew Peak Chew; Sangeun Kim; Sun-Hee Ahn; Laura Palmer; Lujain Aloum; Giacomo Stanzani; Oksana Malanchuk; Michael R. Duchen; Mervyn Singer; et al. (Molecular and Cellular Biochemistry, 2019)

PET imaging study of brown adipose tissue (BAT) activity in mice devoid of receptor for advanced glycation end products (RAGE) - Yu-Shin Ding; Noeen Malik; Sebastian Mendoza; Daniel Tuchman; Carmen Hurtado Del Pozo; Raquel Lopez Diez; Ann-Marie Schmidt (Journal of Biosciences, 2019)

High-altitude and long-range transport of aerosols causing regional severe haze during extreme dust storms explains why afforestation does not prevent storms - Ping Guo; Shaocai Yu; Liqiang Wang; Pengfei Li; Zhen Li; Khalid Mehmood; Xue Chen; Weiping Liu; Yannian Zhu; Xing Yu; Kiran Alapaty; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Tree rings reveal hydroclimatic fingerprints of the Pacific Decadal Oscillation on the Tibetan Plateau - Lixin Lyu; Ulf Büntgen; Kerstin Treydte; Kailiang Yu; Hanxue Liang; Frederick Reinig; Daniel Nievergelt; Mai-He Li; Paolo Cherubini (Climate Dynamics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

IDH-1 deficiency induces growth defects and metabolic alterations in GSPD-1-deficient Caenorhabditis elegans - Hung-Chi Yang; Hsiang Yu; You-Cheng Liu; Tzu-Ling Chen; Arnold Stern; Szecheng J. Lo; Daniel Tsun-Yee Chiu (Journal of Molecular Medicine, 2019)

Water Cooperation Priorities in the Lancang-Mekong River Basin Based on Cooperative Events Since the Mekong River Commission Establishment - Yan Feng; Wenling Wang; Daniel Suman; Shiwei Yu; Daming He (Chinese Geographical Science, 2019)

Current status of the Botryosphaeriaceae in Australia - Treena I. Burgess; Yu Pei Tan; Jeff Garnas; Jacqueline Edwards; Kelly A. Scarlett; Lucas A. Shuttleworth; Rosalie Daniel; Elizabeth K. Dann; Louisamarie E. Parkinson; Quang Dinh; Roger G. Shivas; Fahimeh Jami (Australasian Plant Pathology, 2019)

Science questions and knowledge gaps to study microbial transport and survival in Asian and African dust plumes reaching North America - Andrew C. Schuerger; David J. Smith; Dale W. Griffin; Daniel A. Jaffe; Boris Wawrik; Susannah M. Burrows; Brent C. Christner; Cristina Gonzalez-Martin; Erin K. Lipp; David G. Schmale III; Hongbin Yu (Aerobiologia, 2018)

The relative importance of space compared to topography increases from rare to common tree species across latitude - Yue‐Hua Hu; Daniel J. Johnson; Xiang‐Cheng Mi; Xu‐Gao Wang; Wan‐Hui Ye; Yi‐De Li; Ju‐Yu Lian; Min Cao (Journal of Biogeography, 2018)
Aim Understanding how spatial distributions of rare and common species are associated with environmental and spatial processes is essential to understanding community assembly. We addressed the following questions: (a) does the relative importance of space and topography vary from rare to common tree species? (b) Are the contributions of topography and space equal? (c) Are the variances explained by topography or space correlated with elevational ranges (ER) at the local scale? (d) Does cell‐size influence those postulated associations? Location China and the Americas. Major taxa studied Tree species. Methods We partitioned the variation in species richness and composition of rare and common tree species by topography and space across a range of extents and grain sizes in eight communities. We calculated contribution ratio ( CR ) between space and topography to quantify their relative importance. We employed Kendall's rank correlation to determine the relation between CR and commonness. Mixed effect models were used to identify the influence of cell‐size on the results. Results The majority of CR values were positively related to increasing commonness, especially for composition. The explained variances by space were always higher than that by topography regardless of commonness. At local scale, variances explained by space or topography were not correlated with ER. Main conclusions Our results indicate that the relative importance of space compared to topography increases from rare to common species across forests. We suggest that future studies of community assembly need to account for both space and topography to adequately describe differences in rare and common species assembly mechanisms at range of spatial extents and grain sizes.

Residential emissions predicted as a major source of fine particulate matter in winter over the Yangtze River Delta, China - Yujie Wu; Peng Wang; Shaocai Yu; Liqiang Wang; Pengfei Li; Zhen Li; Khalid Mehmood; Weiping Liu; Jian Wu; Eric Lichtfouse; Daniel Rosenfeld; John H. Seinfeld (Environmental Chemistry Letters, 2018)

Engineering meets institutions: an interdisciplinary approach to the management of resilience - Nader Naderpajouh; David J. Yu; Daniel P. Aldrich; Igor Linkov; Juri Matinheikki (Environment Systems and Decisions, 2018)

Both widespread PEP‐CTERM proteins and exopolysaccharides are required for floc formation of Zoogloea resiniphila and other activated sludge bacteria - Na Gao; Ming Xia; Jingcheng Dai; Dianzhen Yu; Weixing An; Shuyang Li; Shuangyuan Liu; Penghui He; Liping Zhang; Zhenbin Wu; Xuezhi Bi; Shouwen Chen; et al. (Environmental Microbiology, 2018)
Summary Bacterial floc formation plays a central role in the activated sludge (AS) process, which has been widely utilized for sewage and wastewater treatment. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. This study demonstrates an additional requirement for a PEP‐CTERM protein in Zoogloea resiniphila , a dominant AS bacterium harboring a large exopolysaccharide biosynthesis gene cluster. Two members of a wide‐spread family of high copy number‐per‐genome PEP‐CTERM genes, transcriptionally regulated by the RpoN sigma factor and accessory PrsK‐PrsR two‐component system and at least one of these, pepA , must be expressed for Zoogloea to build the floc structures that allow gravitational sludge settling and recycling. Without PrsK or PrsR, Zoogloea cells were planktonic rather than flocculated and secreted exopolysaccharides were released into the growth broth in soluble form. Overexpression of PepA could circumvent the requirement of rpoN , prsK and prsR for the floc‐forming phenotype by fixing the exopolysaccharides to bacterial cells. However, overexpression of PepA, which underwent post‐translational modifications, could not rescue the long‐rod morphology of the rpoN mutant. Consistently, PEP‐CTERM genes and exopolysaccharide biosynthesis gene cluster are present in the genome of the floc‐forming Nitrospira comammox and Mitsuaria strain as well as many other AS bacteria.

Spatial and temporal distributions of air pollutant emissions from open crop straw and biomass burnings in China from 2002 to 2016 - Khalid Mehmood; Shucheng Chang; Shaocai Yu; Liqiang Wang; Pengfei Li; Zhen Li; Weiping Liu; Daniel Rosenfeld; John H. Seinfeld (Environmental Chemistry Letters, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Temporal variability in composition and fluxes of Yellow River particulate organic matter - Shuqin Tao; Timothy I. Eglinton; Liang Zhang; Zhiwei Yi; Daniel B. Montluçon; Cameron McIntyre; Meng Yu; Meixun Zhao (Limnology and Oceanography, 2018)
This study examines temporal variations of the abundance and carbon isotopic characteristics of particulate organic carbon (POC) and specific‐source compounds in the context of hydrological variability in the Yellow River. The content and bulk carbon isotopic characteristics ( 13 C and 14 C) of POC were relatively uniform over the hydrologic (seasonal) cycle. We attribute these temporally invariant geochemical characteristics to the dominant contribution of loess material to the suspended particulate matter (SPM). In contrast, molecular‐level signals revealed that hydrologic conditions exert a significant influence on the proportional contributions of petrogenic and especially fresh plant‐derived OC, while pre‐aged soil OC is mobilized via deeper erosion processes (e.g., gully erosion, mudslides) and is independent of hydrodynamics and surface runoff. A coupled biomarker‐isotope mixing model was applied to estimate the time‐varying supply of contemporary/modern biomass, pre‐aged soil, and fossil OC components to Chinese marginal seas from the Yellow River. We found that natural (e.g., precipitation) and human‐induced (e.g., water and sediment regulation) variations in hydrological regime strongly influence the flux with the magnitude of the corresponding annual fluxes of POC ranging between 0.343 ± 0.122 Mt yr −1 and 0.581 ± 0.213 Mt yr −1 , but less strongly infleunce proportions of the different OC constituents. Inter‐annual differences in pre‐aged soil and fossil OC fluxes imply that extreme climate events (e.g., floods) modulate the exhumation and export of old carbon to the ocean, but the OC homogeneity in the pre‐aged mineral soil‐dominated watersheds facilitates robust predictions in terms of OC transport dynamics in the past (sediment cores) and in the future.

Prolylcarboxypeptidase deficiency is associated with increased blood pressure, glomerular lesions, and cardiac dysfunction independent of altered circulating and cardiac angiotensin II - Christoph Maier; Ines Schadock; Philipp K. Haber; Jan Wysocki; Minghao Ye; Yashpal Kanwar; Christopher A. Flask; Xin Yu; Brian D. Hoit; Gregory N. Adams; Alvin H. Schmaier; Michael Bader; et al. (Journal of Molecular Medicine, 2017)

Atrazine contamination in agricultural soils from the Yangtze River Delta of China and associated health risks - J. T. Sun; L. L. Pan; Yu Zhan; Daniel C. W. Tsang; L. Z. Zhu; X. D. Li (Environmental Geochemistry and Health, 2017)

Colletotrichum species in Australia - Roger G. Shivas; Yu Pei Tan; Jacqueline Edwards; Quang Dinh; Aaron Maxwell; Vera Andjic; José R. Liberato; Chris Anderson; Dean R. Beasley; Kaylene Bransgrove; Lindy M. Coates; Karren Cowan; et al. (Australasian Plant Pathology, 2016)

Robertsonian translocations modify genomic distribution of γH2AFX and H3.3 in mouse germ cells - Shawn Fayer; Qi Yu; Joongbaek Kim; Sanny Moussette; R. Daniel Camerini-Otero; Anna K. Naumova (Mammalian Genome, 2016)

High-mobility group box 1 in multiple sclerosis - Zohara Sternberg; Daniel Sternberg; Trevor Chichelli; Allison Drake; Neel Patel; Chana Kolb; Kailash Chadha; Jinhee Yu; David Hojnacki (Immunologic Research, 2016)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Molecular evolution and functional divergence of X-intrinsic protein genes in plants - Jelli Venkatesh; Jae-Woong Yu; Daniel Gaston; Se Won Park (Molecular Genetics and Genomics, 2015)

Population genetic data of a model symbiotic cnidarian system reveal remarkable symbiotic specificity and vectored introductions across ocean basins - Daniel J. Thornhill; Yu Xiang; D. Tye Pettay; Min Zhong; Scott R. Santos (Molecular Ecology, 2013)
The Aiptasia–Symbiodinium symbiosis is a promising model for experimental studies of cnidarian–dinoflagellate associations, yet relatively little is known regarding the genetic diversity of either symbiotic partner. To address this, we collected Aiptasia from 16 localities throughout the world and examined the genetic diversity of both anemones and their endosymbionts. Based on newly developed SCAR markers, Aiptasia consisted of two genetically distinct populations: one Aiptasia lineage from Florida and a second network of Aiptasia genotypes found at other localities. These populations did not conform to the distributions of described Aiptasia species, suggesting that taxonomic re‐evaluation is needed in the light of molecular genetics. Associations with Symbiodinium further demonstrated the distinctions among Aiptasia populations. According to 18S RFLP , ITS 2 ‐ DGGE and microsatellite flanker region sequencing, Florida anemones engaged in diverse symbioses predominantly with members of Symbiodinium Clades A and B, but also C, whereas anemones from elsewhere harboured only S. minutum within Clade B. Symbiodinium minutum apparently does not form a stable symbiosis with other hosts, which implies a highly specific symbiosis. Fine‐scale differences among S. minutum populations were quantified using six microsatellite loci. Populations of S. minutum had low genotypic diversity and high clonality ( R = 0.14). Furthermore, minimal population structure was observed among regions and ocean basins, due to allele and genotype sharing. The lack of genetic structure and low genotypic diversity suggest recent vectoring of Aiptasia and S. minutum across localities. This first ever molecular‐genetic study of a globally distributed cnidarian and its Symbiodinium assemblages reveals host–symbiont specificity and widely distributed populations in an important model system.

Silicic acid supplied to coastal diatom communities influences cellular silicification and the potential export of carbon - Colleen A. Durkin; Sara J. Bender; Kit Yu Karen Chan; Kelsey Gaessner; Daniel Grünbaum; E. Virginia Armbrust (Limnology and Oceanography, 2013)
Microcosm experiments were conducted along the Washington and Oregon coasts in May 2009, May 2010, and July 2010 to determine whether variation in the supply of silicic acid from the Columbia River could influence the silicification and sinking potential of coastal diatom blooms. The chlorophyll a concentration increased similarly in communities incubated with added nitrate or both nitrate and silicic acid, indicating that growth was limited by nitrate availability. Communities that grew in the treatment with added silicic acid and nitrate were more silicified than communities in the treatment with only nitrate added. No difference in community composition was detected between these treatments in three out of four experiments. Isolates of Minutocellus , Cylindrotheca , Thalassiosira , and Odontella were obtained from the microcosm experiment conducted in May 2010 and were maintained in the laboratory in 20 µmol L −1 silicic acid. All four diatom isolates contained ∼ 2.5 times more silica per cell when silicic acid concentration in the media was increased to 80 µmol L −1 . The intensity of a fluorescent cellular stain of newly precipitated silica (2‐(4‐pyridyl)‐5{[4‐dimethylaminoethyl‐aminocarbamoyl)‐methoxy]phenyl}oxazole) strongly correlated with silica content among species, but was a less sensitive indicator of changing silicification within a single species. Changes in silicification were not correlated with changes in the transcript abundance of silicic acid transporters. Sinking rates increased roughly 2‐fold for cells that contained ∼ 2.5 times more silica. Variation in silicic acid supply alters the silicification of nitrate‐fueled coastal diatom blooms and the potential sink of carbon from coastal zones.

Ocean acidification induces budding in larval sea urchins - Kit Yu Karen Chan; Daniel Grünbaum; Maj Arnberg; Michael Thorndyke; Sam T. Dupont (Marine Biology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

The influence of oxytocin administration on responses to infant faces and potential moderation by OXTR genotype - Abigail A. Marsh; Henry H. Yu; Daniel S. Pine; Elena K. Gorodetsky; David Goldman; R. J. R. Blair (Psychopharmacology, 2012)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Simulation of soil loss processes based on rainfall runoff and the time factor of governance in the Jialing River Watershed, China - Lei Wu; Tian-yu Long; Xia Liu; Daniel Mmereki (Environmental Monitoring and Assessment, 2012)

Deletion of Siah-interacting protein gene in Drosophila causes cardiomyopathy - Michelle E. Casad; Lin Yu; Joseph P. Daniels; Matthew J. Wolf; Howard A. Rockman (Molecular Genetics and Genomics, 2012)

Improved survival among patients with base of tongue and tonsil cancer in the United States - Guo-Pei Yu; Vikas Mehta; Daniel Branovan; Qiang Huang; Mia Hashibe; Zuo-Feng Zhang; Stimson P. Schantz (Cancer Causes & Control, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Mefloquine Damage Vestibular Hair Cells in Organotypic Cultures - Dongzhen Yu; Dalian Ding; Haiyan Jiang; Daniel Stolzberg; Richard Salvi (Neurotoxicity Research, 2011)

A phylogeny of Photinia sensu lato (Rosaceae) and related genera based on nrITS and cpDNA analysis - Wei Guo; Yi Yu; Ru-jiang Shen; Wen-bo Liao; Siew-wai Chin; Daniel Potter (Plant Systematics and Evolution, 2011)

Oxytocin improves specific recognition of positive facial expressions - Abigail A. Marsh; Henry H. Yu; Daniel S. Pine; R. J. R. Blair (Psychopharmacology, 2010)

Can we see a cohort effect on survival of Steller sea lions ( Eumetopias jubatus) at Kozlova Cape rookery (eastern Kamchatka, Russia)? - Alexander M. Burdin; Daniel R. Hennen; Donald G. Calkins; Vladimir N. Burkanov; Victor S. Nikulin; Tatiana Yu. Lisitsina (Marine Mammal Science, 2009)
Steller sea lions ( Eumetopias jubatus ) have experienced a decline in Russia as well as the United States. The causes for the decline of the Russian population may or may not overlap the causes of the decline in Alaska. The demographics of the Russian population are not well understood and are an area of interest for scientists wishing to compare and contrast the Alaskan and Russian stocks. This study uses a unique observational system to assess survival by age at a small rookery on the Kamchatka Peninsula, Kozlova Cape. We proceeded under the hypothesis that changes in environmental conditions between years would produce noticeable differences in survival of pups born in those years. We found no evidence to support our hypothesis, but did find some differences from the Alaskan population in estimated survival for the juvenile stage class. This study also provides some of the history of Steller sea lions in Russia for context.

Number of aberrant crypt foci associated with adiposity and IGF1 bioavailability - Helen Swede; Thomas E. Rohan; Herbert Yu; Joseph C. Anderson; Richard G. Stevens; Jane Brokaw; Joel Levine; Bruce M. Brenner; Carl D. Malchoff; Valerie B. Duffy; Devon C. Pleau; Daniel W. Rosenberg (Cancer Causes & Control, 2009)

Capillary isotachophoresis study of lipoprotein network sensitive to apolipoprotein E phenotype. 2. ApoE and apoC-III relations in triglyceride clearance - Alexander D. Dergunov; Anne Ponthieux; Maxim V. Mel’kin; Daniel Lambert; Olga Yu. Sokolova; Nadir M. Akhmedzhanov; Sophie Visvikis-Siest; Gerard Siest (Molecular and Cellular Biochemistry, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Purification and properties of Sandercyanin, a blue protein secreted in the mucus of blue forms of walleye, Sander vitreus - Chi-Li Yu; Daniel Ferraro; S. Ramaswamy; Mark H. Schmitz; Wayne F. Schaefer; David T. Gibson (Environmental Biology of Fishes, 2008)

Chelerythrine treatment influences the balance of pro- and anti-apoptotic signaling pathways in the remote myocardium after infarction - Gregor Simonis; Stephan Wiedemann; Kerstin Schwarz; Torsten Christ; Daniel G. Sedding; Xinjian Yu; Rainer Marquetant; Ruediger C. Braun-Dullaeus; Ursula Ravens; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2008)

Methods to impute missing genotypes for population data - Zhaoxia Yu; Daniel J. Schaid (Human Genetics, 2007)

Potentially Reduced Exposure Cigarettes Accelerate Atherosclerosis: Evidence for the Role of Nicotine - Daniel F. Catanzaro; Ying Zhou; Rong Chen; Fangmin Yu; Sarah E. Catanzaro; Mariana S. De Lorenzo; Kotha Subbaramaiah; Xi Kathy Zhou; Domenico Pratico; Andrew J. Dannenberg; Babette B. Weksler (Cardiovascular Toxicology, 2007)

Pharmacodynamics of Antiretroviral Agents in HIV-1 Infected Patients: Using Viral Dynamic Models that Incorporate Drug Susceptibility and Adherence - Hulin Wu; Yangxin Huang; Edward P. Acosta; Jeong -Gun Park; Song Yu; Susan L. Rosenkranz; Daniel R. Kuritzkes; Joseph J. Eron; Alan S. Perelson; John G. Gerber (Journal of Pharmacokinetics and Pharmacodynamics, 2006)

The rat Na+–sulfate cotransporter rNaS2: functional characterization, tissue distribution, and gene (slc13a4) structure - Paul A. Dawson; Katrina J. Pirlo; Sarah E. Steane; Kim A. Nguyen; Karl Kunzelmann; Yu Ju Chien; Daniel Markovich (Pflügers Archiv - European Journal of Physiology, 2005)

Respiratory effect of acute and subacute exposure to endotoxin-contaminated metal working fluid (MWF) aerosols on Sprague-Dawley rats - Cheol-Hong Lim; Il Je Yu; Hyeon-Young Kim; Seung-Bae Lee; Min-Gu Kang; Daniel R. Marshak; Chang-Kiu Moon (Archives of Toxicology, 2005)

pH-Triggered Release of Macromolecules from Spray-Dried Polymethacrylate Microparticles - Daniel S. Kohane; Daniel G. Anderson; Christine Yu; Robert Langer (Pharmaceutical Research, 2003)

Water isotopic and hydrochemical evolution of a lake chain in the northern Great Plains and its paleoclimatic implications - Zicheng Yu; Emi Ito; Daniel R. Engstrom (Journal of Paleolimnology, 2002)

Allelic and locus heterogeneity in autosomal recessive gelatinous drop-like corneal dystrophy - Zhaoxia Ren; Pei-Yu Lin; Gordon K. Klintworth; Fumino Iwata; Francis L. Munier; Daniel F. Schorderet; Leila El Matri; Veena Theendakara; Surendra Basti; Madhukar Reddy; Fielding J. Hejtmancik (Human Genetics, 2002)

Age-specific Effects of Novel Mutations in Drosophila Melanogaster I. Mortality - Lev Yu. Yampolsky; Louise E. Pearse; Daniel E.L. Promislow (Genetica, 2000)

Interaction of DNA-binding proteins with the 5′-flanking region of a cytokinin-responsive cucumber hydroxypyruvate reductase gene - Ge Jin; Maria C. Davey; John R. Ertl; Rui Chen; Zhu-tian Yu; Steven G. Daniel; Wayne M. Becker; Chong-maw Chen (Plant Molecular Biology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Biochemical and immunological characterization of genetic variants of phosphoglucose isomerase from mouse - Daniel J. Charles; Chi-Yu Lee (Biochemical Genetics, 1980)